Laser Material Processing of Medical Titanium: Titanium boxes for hermetic transport of medical implants. Issue 1 (21st January 2016) - Patschger, Andreas; Hopf, Andreas; Güpner, Michael; Bliedtner, Jens
Abstract: Titanium is considered to be the most attractive metallic material for medical applications such as dental implants. Furthermore, it can be used to build up gas‐tight and sterile transport boxes in order to maintain the sterility of the implants during shipment. For this purpose laser processes were investigated and led to low‐impact and clean assembly of the transport boxes. The following article provides an overview of suitable laser remote processes and, by means of an assembly example, shows how laser material processing with its diversity can support the sterile transport of medical implants.